Analysis of the Association of A Heat Shock Protein70-1 Gene Promoter Polymorphism With Myocardial Infarction and Coronary Risk Traits. Issue 4 (1998) - Bolla, M.K.; Miller, G.J.; Yellon, D.M.; Evans, A.; Luc, G.; Cambou, J.P.; Arveiler, D.; Cambien, F.; Latchman, D.S.; Humphries, S.E.; Day, I.N.M.
Abstract : Heat shock proteins (HSP) are induced during coronary ischaemia, and abnormal expression of one HSP gene may cause hypertension in rats, We examined association of a promoter polymorphism in the major stress-inducible hsp70 gene (hsp70-1 or HSP70A1) on chromosome 6 (p21.3) with coronary disease traits, This C→A base substitution (AAAC CCC) is at nucleotide position -110 in the heat shock transcription factor binding site (heat shock element, HSE). The first study sample (ECTIM), recruited from Belfast and three centres in France, consisted of 578 myocardial infarction cases and 698 agematched controls. The frequency of the A-110 allele was 0.381 (95% CI=0.35-0.41) and 0.384 (95% CI=0.36-0.41) in cases and controls respectively, Homozygotes for the rarer A-110 allele had a higher BMI (27.3 kg/m 2 ±3.9) compared with homozygotes for the common C-110 allele (26.3 kg/m 2 ±3.3), The rarer homozygotes were shorter and heavier than the common homozygotes. A follow-up study involved 1431 healthy, middle aged men from the UK (NPHSII group). The frequency of the A-110 allele was 0.385 (95% CI=0.37 -0.40), and there was no association of genotype with BMI. Thus there appears to be no strong association of the Hsp70-1 promoter polymorphism with risk of myocardial infarction, BMI or any coronary disease traits analysed here.